The future of hard coal compared to other energy carriers. (July 2018) - Manowska, Anna; Rybak, Aurelia
Abstract: Primary energy sources in Poland are mostly fossil fuels, such as: hard coal, brown coal, natural gas, petroleum and other sources, which include, for instance, renewable energy sources. However, the major role is played by hard and brown coals. For many years hard coal has guaranteed energy security as well as energy independence and the forecast about the demand for net electrical energy [TWh] developed by the Ministry for Energy shows that coal will remain the leading source. Polish mining has been one of the most important industrial sectors for a long time, but for the last several years it has been in some dire straits. One of the main problems of the mining industry is lack of national strategy concerning the future of the fuel and energy sector, especially the energy mix.